PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATA PELAJARAN IPS KELAS VII DI SMP - Rizkya Irvan Reynaldy; Junaidi H Matsum; Sri Buwono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The research aims to determine the Learning Outcomes of Problem Based Learning Models in Social Studies of Class VII Students of Junior High School 1 Mandor. The research method used in this research is Experiment with Quasi Experimental design and Posttest-only control design. Based on the result of the hypothesis obtained t count & gt; t table (5,532 & gt;2,00), which mean Ho rejected. This show that there is a significant difference between the learning outcomes using a problem based learning models and a conventional models, if there is a significant difference then the treatment will affect significantly. So it can be concluded that applying of a Problem-Based Learning Model can affect the learning outcomes in IPS subject students class VII SMP Negeri 1 Mandor, can be seen from Effect Size Problem Based Learning Model on IPS Subjects Students Class VII SMP Negeri 1 Mandor of 1,46 included in the category of high. Keywords: Problem Based Learning Model, Social Studies